(3QSGdI aj GdefWbs
(3ChdgG (B:s
(3GdMeO Gddg GdYdi GdajGVi hHYO agPg JMag WdGH cd ReGf HSe Gddg GdQMef GdQMje eSJYjfkG Hg heJHQckG dg heJjefkG Hg s
(3BNQgG (B:s
(3EP dG jLH ajgG MQa BjGJ GdbQBf agi CNU eWdbkG ef GdeYLRGJ gPG BNQ eG ChQOfG HjGfg hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs